Requirements for effective investigation and learning after suicide: the views of persons with lived experience and professionals - Elin Fröding; Charles Vincent; Boel Andersson-Gäre; Åsa Westrin; Åsa Westrin; Axel Ros (Frontiers in Health Services)
ObjectiveThis study aims to provide a deeper understanding of what persons with lived experience and professionals with experience of patient safety, suicide research, and investigations consider to be most important in investigations of healthcare before suicide to learn and improve the care of suicidal patients.MethodThis is a qualitative study based on 15 semistructured interviews with persons with lived experience of suicidality and professionals. Thematic analysis was used.ResultsThe persons with lived experience and the professionals agreed that a holistic approach to the investigations is crucial. They should embrace a longer period of time, involve family and significant others, integrate the perspective and expectations of the patient, and analyze factors of significance for suicidality, suicide prevention, and safety. There is a need to improve the investigations through the involvement of all stakeholders and actors, securing competence in the investigation team and prioritizing cases to investigate.ConclusionsSubstantial changes in the approach and performance of investigations of suicide in healthcare are needed to make these investigations valuable for increasing the safety of the care of suicidal patients. A holistic perspective during the analysis is crucial for understanding the suicidal process, the interacting factors, and the care process preceding suicide. Competencies in suicidality, suicide prevention, and patient safety must be included in the analysis team to ensure high quality and relevance. To improve the value of these investigations, we suggest establishing a template based on current knowledge to ensure attention to variables of significance for a safe care of suicidal patients.